Über die Fläche in bilinear-metrischem projektivem Raum - Stiklakytė, L. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Л. Стиклаките. О поверхностях билинейно-метрического проективного пространстваL. Stiklakytė. Apie dvitiesiškai-metrinės projektyvinės erdvės paviršius